Printed technology as a comprehensive paradigm for circular economy of electronics - Tatiana Robledo-Mahón; Sonia Gómez-Gijón; Álvaro Blasco; Victor Toral; Francisco J. Romero; Elisabet Aranda; Almudena Rivadeneyra (npj Materials Sustainability)
Abstract The increasing demand for high-performance electronics and sustainability challenges, requires innovative recycling technologies. This study explores the potential of fungal microorganisms in degrading conductive inks, promoting their circular economy integration. Taking advantage of the ability of fungi to process complex compounds, seven fungal strains—Trametes versicolor, Funalia floccosa, Pycnoporus cinnabarinus, Aspergillus niger HM81, Aspergillus versicolor HM30, Scopulariopsis brevicaulis HM03 and Thielavia sp. HM70—were tested to degrade copper-based conductive papers (CPs) for 60 days. Post-incubation assessments include gravimetric approach, oxidoreductase enzyme production, attenuated total reflectance-Fourier transform infrared (ATR-FTIR) and X-Ray photoelectron spectroscopy (XPS). The results revealed that all the strains reduced the weight by more than 50% and modified the cellulosic composition, being P. cinnabarinus the strain that showed the best results with 77.8% reduced weight. This technique significantly enhances the recyclability of high-performance, yet polluting materials, reducing their environmental impact, and minimising electronic waste.